2021
DOI: 10.1002/jso.26768
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and evolving prescribing practice of opioid and non‐opioid analgesics in patients undergoing lymphadenectomy for cutaneous malignancy

Abstract: Background and Objectives: Opioids are commonly prescribed following surgery and can lead to persistent opioid use. We assessed changes in prescribing practices following an opioid education initiative for patients undergoing lymphadenectomy for cutaneous malignancy.Methods: A single-institution retrospective study of all eligible patients (3/2016-3/ 2020) was performed.Results: Indications for lymphadenectomy in 328 patients were metastatic melanoma (84%), squamous cell carcinoma (10%), and Merkel cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…12,13 A follow-up study 1 year later found that the educational interventions were associated with decreased inpatient and discharge opioid prescribing. 19,37 While other institutions have shown similar first-pass gains with opioid reduction programs, 38 this study is the first to our knowledge to show an association with sustained reductions in opioid consumption and dissemination over 2 iterative revisions of established pathways, resulting in attainment of a previously unrealistic goal of opioid-free discharge after pancreatic resection.…”
Section: Discussionmentioning
confidence: 67%
“…12,13 A follow-up study 1 year later found that the educational interventions were associated with decreased inpatient and discharge opioid prescribing. 19,37 While other institutions have shown similar first-pass gains with opioid reduction programs, 38 this study is the first to our knowledge to show an association with sustained reductions in opioid consumption and dissemination over 2 iterative revisions of established pathways, resulting in attainment of a previously unrealistic goal of opioid-free discharge after pancreatic resection.…”
Section: Discussionmentioning
confidence: 67%
“…We found that robotic PD was associated with decreased inpatient opioid use with similar postoperative pain scores. In both robotic PD and open PD groups, we found relatively low opioid usage due to several iterative changes we have made across our Department of Surgical Oncology for postoperative analgesia across disease sites 5,13,14,18–26 . Lower inpatient opioid use then led to reduced discharge prescription volumes overall.…”
Section: Discussionmentioning
confidence: 93%
“…In both robotic PD and open PD groups, we found relatively low opioid usage due to several iterative changes we have made across our Department of Surgical Oncology for postoperative analgesia across disease sites. 5,13,14,[18][19][20][21][22][23][24][25][26] Lower inpatient opioid use then led to reduced discharge prescription volumes overall. On multivariate analysis, the robotic approach, absence of a pancreatic fistula and older age were associated with decreased OME.…”
Section: Discussionmentioning
confidence: 99%